Data update algorithm based on secure network coding in cloud environment - Hao WU; Cheng-zhe LAI; Jiu-lun FAN; Jian-hua LIU (Tongxin xuebao)
In the cloud environment for data storage,the use of secure network coding technology can be a good solution to the data privacy and reliability issues.However,each coding block usually has a high correlation after network coding,very few updates to the file need to be re-encoded which is extremely easy to cause information leakage and serious consumption of system resources.To solve this problem,a network coding cloud storage data updating algorithm was proposed.Just by sending files change difference matrix,the storage node could update parts of the coding block accordingly which could complete the entire update files.Experimental results show that compared with RS coding and Tornado coding,the algorithm can not only ensure data security,but also greatly improve the efficiency of data update and data reconstruction.